Matrin3 binds directly to intronic pyrimidine‐rich sequences and controls alternative splicing. (11th July 2017) - Uemura, Yuri; Oshima, Takuya; Yamamoto, Munetaka; Reyes, Charles Jourdan; Costa Cruz, Pedro Henrique; Shibuya, Toshiharu; Kawahara, Yukio
Abstract : Matrin3 is an RNA‐binding protein that is localized in the nuclear matrix. Although various roles in RNA metabolism have been reported for Matrin3, in vivo target RNAs to which Matrin3 binds directly have not been investigated comprehensively so far. Here, we show that Matrin3 binds predominantly to intronic regions of pre‐mRNAs. Photoactivatable Ribonucleoside‐Enhanced Cross‐linking and Immunoprecipitation (PAR‐CLIP) analysis using human neuronal cells showed that Matrin3 recognized pyrimidine‐rich sequences as binding motifs, including the polypyrimidine tract, a splicing regulatory element. Splicing‐sensitive microarray analysis showed that depletion of Matrin3 preferentially increased the inclusion of cassette exons that were adjacent to introns that contained Matrin3‐binding sites. We further found that although most of the genes targeted by polypyrimidine tract binding protein 1 (PTBP1) were also bound by Matrin3, Matrin3 could control alternative splicing in a PTBP1‐independent manner, at least in part. These findings suggest that Matrin3 is a splicing regulator that targets intronic pyrimidine‐rich sequences. Abstract : In this study, we show that Matrin3, an RNA‐binding protein, binds predominantly to intronic regions of pre‐mRNAs. PAR‐CLIP analysis using human neuronal cells showed that Matrin3 recognized pyrimidine‐rich sequences as binding motifs, including the polypyrimidine tract, a splicing regulatory element. Depletion of Matrin3 preferentially increased the inclusion of cassette exons that were adjacent to introns that contained Matrin3‐binding sites, which suggests that Matrin3 is a splicing regulator.